Waste Management in Masnana Village, Namrole Subdistrict, South Buru Regency - Salakory, Melianus; Lesnussa, Marlen; Tetelepta, Edward Gland (JENDELA PENGETAHUAN, 2024)
This study aims to identify and analyze waste management in Masnana Village, Namrole District, South Buru Regency. The main focus of the research is the behavior of the community in managing waste and the stages of waste management from generation to final disposal. Data were collected through observation, interviews, questionnaires, and documentation. The results show that the main sources of waste in Masnana Village come from households, restaurants, schools, and lodging, as well as natural factors and human activities. Waste generation is measured by weight and volume per person per day, with an average waste weight of 0.35 kg and volume of 25 liters per person per day. The types of waste produced are divided into organic and inorganic waste, with the majority of organic waste still being burned (73.33%) and most inorganic waste also being burned (66.66%). On-site waste management involves the reuse of paint cans and beverage bottles. Waste collection is carried out to temporary disposal sites using a sorting bin system. Organic waste processing is carried out through composting, although many residents still prefer burning. Electronic waste is managed by selling, repairing, or burying it. Final disposal is handled by the Public Works Department to the Piyungan landfill. This study highlights the importance of community participation in waste management to reduce environmental impact and extend landfill life